The Rural and Agricultural Roots of the Tunisian Revolution: When Food Security Matters - Gana, Alia (The International Journal of Sociology of Agriculture and Food, 2012)
Originating in rural areas, the popular uprising that led to the Tunisian revolution of 14 January 2011 has shed light on the growing social and regional disparities that have characterized development dynamics in Tunisia. While fa- vouring the reallocation of resources to coastal areas to the detriment of interior and agricultural regions, liberalization processes since the late 1980s also fostered export-oriented agricultural development strategies, based on the promotion of large-scale agricultural enterprises and irrigated farming. As a result, imports of grains and animal feed have come to represent a growing source of commercial balance deficit and of financial pressure on public budgets, particularly since the food crisis of 2008. On the other hand, decreasing farm subsidies, higher produc- tion costs, growing farmers’ indebtedness, have importantly reduced the repro- duction capacity of a large fraction of farms, particularly in the rain-fed agricul- ture sector. As rural outmigration and non-farm employment opportunities have been declining, small farms have become survival spaces for jobless household members, increasing the pressure on family resources and exacerbating social frustrations. While rising food prices were not the only cause of recent uprisings in Tunisia, processes of agricultural restructuring during the past 20 years contrib- uted importantly to fuel the revolutionary dynamics, thus giving a political di- mension to food issues. As demonstrated by the rise of farmers’ protest movement (land occupations, contestation of farmers unions, refusal to pay for irrigation water), structural change allowing for an increased control of economic resources by local farm producers is needed, but will fundamentally depend on the effec- tiveness of current process of ‘democratic’ transition in Tunisia.